REFORMULATION OF AMNESTY AND ABOLITION IN THE STATE SYSTEM IN INDONESIA - Lubis, Mhd Ansor; Firdaus, Aras; Harahap, Muslim; Lawali Hasibuan, H. Abdul; Elisa Munthe, Gerald (NOMOI Law Review, 2025)
The granting of amnesty and abolition is a presidential prerogative. This is regulated in the 1945 Constitution. Although it is a presidential prerogative, the question remains whether the granting of amnesty and abolition by the president recently has been in accordance with statutory regulations. This study uses a normative juridical research method with a statutory, conceptual, and comparative approach. The results show that amnesty and abolition are legal instruments derived from the president's constitutional authority as head of state. Both instruments function as extraordinary forms of forgiveness or waiver of legal charges, as they concern the interests of the state, reconciliation, and political and social stability. However, in Indonesian constitutional practice, the granting of amnesty and abolition often sparks debate. On the one hand, the president's authority is seen as a manifestation of the prerogative recognized in the constitution; on the other hand, there are concerns about the emergence of impunity practices that could undermine the rule of law and the independence of the judiciary. Therefore, reformulating the concepts of amnesty and abolition within the framework of the state system is a necessity to ensure a balance between state interests and upholding the principles of the rule of law.